PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI PEMODERASI - Meidy Aurora Caesaria; Sugi Suhartono (Jurnal Akuntansi, 2023)
Firm value is an important aspect to describe the success of company owners and shareholders which is often associated with stock prices which are often used as a tool to influence investors' views of a company. This study aims to determine the effect of financial performance such as the level of profitability, leverage, and liquidity on firm value and how the effect of audit quality in moderating the effect of financial performance on firm value in food and beverage sub-sector companies listed on the IDX in 2018 – 2021.  The object of this study is 27 food and beverage sub-sector companies listed on the IDX in 2018 – 2021 so that 108 observational data were obtained. This research shows that it is proven that profitability has a positive influence on company value and audit quality is able to strengthen the positive influence of profitability on firm value. While leverage and liquidity have not been shown to have a positive effect on the value of the company. Quality audits are also unable to moderate the positive effect of leverage and liquidity on firm value.